PENGARUH FINGER PAINTING TERHADAP KEMAMPUAN MOTORIK HALUS PADA ANAK USIA 5-6 TAHUN DI TK FLAMBOYAN KABUPATEN KUANTAN SINGINGI - Wahyuni Siti Rokayati; Wilson '; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The capacity of the small motor is organizing the use of a group of small muscles like the fingers and hands that often requires precision and eye-hand coordination, these skills include the use of the tools to work and small objects or control of the machine, for example in the drawing. Finger Painting is the type of activity create an image that is done by scraping the dough color (color porridge) directly with your fingers freely above the plane of the image, limit finger here are all the fingers, palms, wrists up. The hypothesis of this study is a significant difference Finger Painting on the fine motor skills in drawing in children aged 5-6 years at Tk Flamboyant Village Resources Datar Regency Kuantan District of Singingi Singingi. Comparison of before and after, it can be seen that most of the fine motor skills in a drawing activity before and after treatment increased initially categorized began to grow, increased to develop according to expectations. To create a statistical test, then tested the prerequisite as much as 3 test requirements, namely: homogeneity, normality test and linearity test. Of the three tests, linearity test does not qualify. Therefore, perform the Wilcoxon test. It can be tested from the Wilcoxon test showed, for n = 17 error level of 5% (test 2 sides), then t table = 35. Therefore the number of levels that are of little value was 0.0 and the value of t table = 35, also 0.0 <35, so Ha is received. Thus, it can be concluded that the finger painting has a significant influence on the fine motoric abilities of children in drawing activities. Means in this penenlitian there are significant fine motor skills in drawing children before and after finger painting in kindergarten Falmaboyant Singingi Kuantan. According to the table acquisition criteria score of N-gain, it is known that the limit of 0.36 in middle category. That is, a modest increase in the fine motor skills of children in activities to draw from pretest to posttest.